Purification and characterization of the human platelet fibrinogen receptor, GpIIb/IIIa complex - (:unkn) unknown (My University, 2005)
İntegrin ailesinin bir üyesi olan GpIIb/IIIa, yapısal olarak fibrinojen gibi adeziv proteinlerle ilişkili trombosit adezyon reseptörüdür. Ligand bağlamak için bir agoniste ihtiyaç duyar ve yapısında konformasyonel bir değişikliğe uğrar. Bu modifikasyona ek olarak, trombosit a-granüllerinden ve yüzey bağlantılı açık kanaliküler sistemden GpIIb/IIIa havuzuna katkı sağlanarak, ligand-bağlama fonksiyonu ve yüzey expresyonu artar. Trombositlerefibrinojen bağlanması trombosit agregasyonu için önemlidir. Trombosit agregasyonu normal hemostas için temeldir ve trombozda da rol oynamaktadır.. Bu çalışmada, sağlıklı insan trombositlerinden GRGDSP-afinite kromatografisi ile GpIIb/IIIa tek adımda saflaştırıldı. Saflaştırılmış GpIIb/IIIa kompleksi ile, GpIIb/IIIa 'ya spesifik ligandlarla bağlanma özelliklerinin çalışmaları yapıldı.

Platelet GpIIb/IIIa is a member of the integrin family of structurally related adhesion receptors, and adhesive proteins, such asfibrinogen. Ligand binding requires platelet activation by an agonist to convert the receptor to a state where it is capable to bind the ligand. In addition to this a modification, induction of the surface expression and ligand-binding function of an additional pool of GpIIb/ Ilia derived from a-granuler membranes and/or surface-connecting open canalicular system are established. Fibrinogen binding to platelets appears to be important for platelet aggregation. Platelet aggregation is essential for normal hemostasis and also plays a role in thrombosis. In this study, we purified GpIIb/IIIa on a single step from normal human platelets by GRGDSP-affinity chromatography. In addition, studies on the characterization of the binding properties to Glib/ Ilia of the specific ligands were carried out with the purified GpIIb/IIIa complex.
İnsan trombosit fibrinojen reseptörü GpIIb/IIIa kompleksinin saflaştırılması ve tanımlanması
Keywords: Farmakoloji ve Eczacılık